Территориальные аспекты формирования и становления кластеров на основе кооперации промышленных предприятий и высших учебных заведений - Шамаева, Н.П. (Культура народов Причерноморья, 2014)
В статье, на примере Удмуртской Республики, рассматриваются механизмы создания
территориальных кластеров, которые обеспечивают мобилизацию имеющихся ресурсов в производство
новых видов конкурентоспособной продукции, что, в свою очередь, обеспечивает получение высокой
прибыли.
Подобные территориальные комплексы включают в свой состав промышленные предприятия,
объединенные по территориальному и отраслевому принципу. Для успешного такого кластера
необходимо организовать эффективное взаимодействие бизнеса, представителей науки,
преподавателей вузов и государства. У статті, на прикладі Удмуртської Республіки, розглядаються механізми створення
територіальних кластерів. Подібні територіальні комплекси включають в свій склад промислові
підприємства, об'єднані за територіальним і галузевим принципом. Для успішного такого кластера
необхідно організувати ефективну взаємодію бізнесу, представників науки, викладачів вузів і держави.
Забезпечення сталого розвитку території передбачає об'єктивну оцінку ситуації, що склалася і
визначення найбільш ефективних варіантів її розвитку. Тут необхідно знайти оптимальний варіант
поєднання інтересів In the article, an example of the Udmurt Republic, the mechanics of regional clusters, which provide
the mobilization of resources in the production of new types of competitive products, which in turn provides a
higher profit. Such territorial complexes include our industrial enterprises, territorial integration and sectoral
principle. For such a successful cluster is necessary to organize effective cooperation between business,
academics, university lecturers and the state.
Cluster theory clearly indicates the close relationship between the cluster and partnership firms'
competitiveness. All companies in the cluster form a single system, which is located in a particular area.
Relationships between enterprises and organizations are built either on the principle of horizontal or vertical
links. In this case, industry, research organizations and higher education institutions, while maintaining formal
independence, create a system of economic relations on the basis of cooperation, giving each other the goods,
services, patents, research and development, labor and other resources. Here, of course, you need to find the
optimal combination of interests.